A spatial analysis of land use and cover change and agricultural performance: evidence from northern Ghana. (17th September 2018) - Haile, Beliyou; Signorelli, Sara; Azzarri, Carlo; Guo, Zhe
Abstract: Using remotely sensed land-cover data in 1994 and 2014, and cross-sectional survey data in 2014, this study examines the association between land use and cover change and agricultural productivity in northern Ghana. We document a significant expansion of crop land and settlements (productive use) at the expense of natural vegetation cover. Land areas converted from natural cover to productive use have higher maize yield (0.17 tons per hectare) and harvest value (1, 021 Ghanaian Cedi) compared with those converted from bare soil to productive cover. Moreover, areas that were covered by shrubs or savannah in 1994 were more productive in 2014 relative to bare soils in 1994. Although our data do not allow us to establish causality, the evidence suggests the importance of past land-cover conditions in affecting current agricultural performance, especially in resource-stricken settings where conservation and restoration practices are not as common.